Medicinal Plants Used in Traditional Management of Cancer in Uganda: A Review of Ethnobotanical Surveys, Phytochemistry, and Anticancer Studies - Omara, Timothy (Evid Based Complement Alternat Med, 2020)
The burden of neoplastic diseases is a significant global health challenge accounting for thousands of deaths. In Uganda, about 32,617 cancer cases were reported in 2018, accompanied by 21,829 deaths. In a view to identify some potential anticancer plant candidates for possible drug development, the current study was designed to compile the inventory of plants with reported anticancer activity used in rural Uganda and the evidences supporting their use in cancer therapy. An electronic survey in multidisciplinary databases revealed that 29 plant species belonging to 28 genera distributed among 24 families have been reported to be used in the management of cancer in Uganda. Anticancer plants were majorly from the families Bignoniaceae (7%), Caricaceae (7%), Fabaceae (7%), Moraceae (7%), and Rutaceae (7%). Most species occur in the wild (52%), though some are cultivated (48%). The growth habit of the plants is as trees (55%) or herbs (45%). Anticancer extracts are usually prepared from leaves (29%), bark (24%), roots (21%), and fruits (13%) through decoctions (53%), as food spices (23%) or pounded to produce ointments that are applied topically (10%). Prunus africana (Hook.f.) Kalkman, Opuntia species, Albizia coriaria (Welw. ex Oliver), Daucus carota L., Cyperus alatus (Nees) F. Muell., Markhamia lutea (Benth.) K. Schum., and Oxalis corniculata L. were the most frequently encountered species. As per global reports, Allium sativum L., Annona muricata L., Carica papaya L., Moringa oleifera Lam., Opuntia species, Prunus africana (Hook.f.) Kalkman, and Catharanthus roseus (L.) G. Don. are the most studied species, with the latter having vincristine and vinblastine anticancer drugs developed from it. Prostate, cervical, breast, and skin cancers are the top traditionally treated malignancies. There is a need to isolate and evaluate the anticancer potential of the bioactive compounds in the unstudied claimed plants, such as Cyperus alatus (Nees) F. Muell., Ficus dawei Hutch., Ficus natalensis Hochst., and Lovoa trichilioides Harms, and elucidate their mechanism of anticancer activity.